2012
DOI: 10.1155/2012/406497
|View full text |Cite
|
Sign up to set email alerts
|

Blocked Atrial Bi/Trigeminy In Utero Evolving in Supraventricular Tachycardia after Birth

Abstract: Transient episodes of fetal bradycardia (heart rate less than 110 bpm) are usually benign and typically result from increased vagal stimulation in the fetus. Causes of sustained fetal bradycardia include sinus bradycardia, blocked atrial bigeminy/trigeminy, high-degree atrioventricular block, and long QT syndrome. We present the case of a 34-year-old Caucasian patient referred to our department for “blocked atrial bigeminy with pseudobradycardia” detected elsewhere at 33 weeks of gestation. A fetal echocardiog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…It was present in only 1 subject (10%), but this corroborates that fetuses with PACs are at risk of developing SVT. 9,12 Martucci et al 17 reported a case study in which the subject was referred with BAB that developed SVT after birth. The subjects with AVB showed fewer other rhythms.…”
Section: Discussionmentioning
confidence: 99%
“…It was present in only 1 subject (10%), but this corroborates that fetuses with PACs are at risk of developing SVT. 9,12 Martucci et al 17 reported a case study in which the subject was referred with BAB that developed SVT after birth. The subjects with AVB showed fewer other rhythms.…”
Section: Discussionmentioning
confidence: 99%
“…Their case also showed a normal rhythm immediately after delivery; however, contrary to our case, trigeminal PACs and supraventricular tachycardia (SVT) developed 11 days after birth [9]. …”
Section: Discussionmentioning
confidence: 65%
“…Martucci et al reported a fetus with pseudobradycardia due to trigeminal PACs on the 33rd week of gestation. Their case also showed a normal rhythm immediately after delivery; however, contrary to our case, trigeminal PACs and supraventricular tachycardia (SVT) developed 11 days after birth [ 9 ].…”
Section: Discussionmentioning
confidence: 65%
“…Our findings suggest that ASA-associated AF abates with resolution of the ASA in extra-uterine adaptation. Notably, Martucci et al [ 35 ] reported a fetus with pseudobradycardia caused by trigeminal PACs at week 33 of pregnancy. Their case also showed a normal rhythm immediately after birth.…”
Section: Discussionmentioning
confidence: 99%